Formation of Multiscale Pattern Structures by Combined Patterning of Nanotransfer Printing and Laser Micromachining - Tae Wan Park; Young Lim Kang; Eun Bin Kang; Seungmin Kim; Yu Na Kim; Woon Ik Park (Nanomaterials, 2023)
Various lithography techniques have been widely used for the fabrication of next-generation device applications. Micro/nanoscale pattern structures formed by lithographic methods significantly improve the performance capabilities of the devices. Here, we introduce a novel method that combines the patterning of nanotransfer printing (nTP) and laser micromachining to fabricate multiscale pattern structures on a wide range of scales. Prior to the formation of various nano-in-micro-in-millimeter (NMM) patterns, the nTP process is employed to obtain periodic nanoscale patterns on the target substrates. Then, an optimum laser-based patterning that effectively engraves various nanopatterned surfaces, in this case, spin-cast soft polymer film, rigid polymer film, a stainless still plate, and a Si substrate, is established. We demonstrate the formation of well-defined square and dot-shaped multiscale NMM-patterned structures by the combined patterning method of nTP and laser processes. Furthermore, we present the generation of unusual text-shaped NMM pattern structures on colorless polyimide (CPI) film, showing optically excellent rainbow luminescence based on the configuration of multiscale patterns from nanoscale to milliscale. We expect that this combined patterning strategy will be extendable to other nano-to-micro fabrication processes for application to various nano/microdevices with complex multiscale pattern geometries.